Extraterritorial effects of territorial self-government decisions - Jančát, Lukáš (Wydawnictwo Uniwersytetu Rzeszowskiego, 2023)
As a result of expanding globalisation, states in various cases, in order to protect different interests and by reference to different principles, increasingly abandon rigid adherence to the principle of non-interference in the internal affairs of other States in the area of prescriptive jurisdiction and reciprocally accept the extension of the effects of individual legal acts issued by another State on their territory. In the conditions of the European Union, this acceptance concerns civil, criminal and administrative matters. It is individual administrative acts that are of particular interest from the point of view of the possibility of acquiring extraterritorial effects, because for several of tchem no specific recognition procedure is required. The aim of this paper is to characterize administrative acts with extraterritorial effects. Then to define the basic regimes for recognition and enforcement of administrative acts and to present examples of their application in the conditions of the Slovak Republic. Lastly to identify examples of administrative acts of local self-government authorities with extraterritorial effects and, following the examples thus identified, to present the regimes of their recognition and enforcement.

W wyniku postępującej globalizacji, państwa w różnych przypadkach, w celu ochrony różnych interesów i odwołując się do różnych zasad, coraz częściej odchodzą od sztywnego przestrzegania zasady nieingerencji w sprawy wewnętrzne innych państw w obszarze jurysdykcji normatywnej i wzajemnie akceptują rozszerzenie skutków poszczególnych aktów prawnych wydanych przez inne państwo na ich terytorium. W warunkach Unii Europejskiej akceptacja ta dotyczy spraw cywilnych, karnych i administracyjnych. To właśnie indywidualne akty administracyjne są szczególnie interesujące z punktu widzenia możliwości wywołania skutków eksterytorialnych, ponieważ w przypadku kilku z nich nie jest wymagana żadna szczególna procedura uznawania . Celem niniejszego artykułu jest scharakteryzowanie aktów administracyjnych o skutkach eksterytorialnych. Następnie zdefiniowanie podstawowych systemów uznawania i wykonywania aktów administracyjnych oraz przedstawienie przykładów ich zastosowania w warunkach Republiki Słowackiej. Wreszcie, wskazanie przykładów aktów administracyjnych organów samorządu terytorialnego o skutkach eksterytorialnych oraz, w oparciu o zidentyfikowane w ten sposób przykłady, przedstawienie systemów ich uznawania i egzekwowania.
Efekty eksterytorialne decyzji samorządu terytorialnego
Keywords: Extraterritorial Administrative Acts; recognition and enforcement of administrative decisions; territorial self-government; eksterytorialne akty administracyjne; uznawanie i wykonywanie decyzji administracyjnych; samorząd terytorialny